2012
DOI: 10.2196/resprot.2329
|View full text |Cite
|
Sign up to set email alerts
|

Web-based Intervention for Postpartum Depression: Formative Research and Design of the MomMoodBooster Program

Abstract: BackgroundPostpartum depression is a significant public health problem affecting approximately 13% of women. There is strong evidence supporting Cognitive Behavioral Therapy (CBT) for successful psychosocial treatment. This treatment model combines cognitive and behavioral strategies to address pessimism, attributions for failure, low self-esteem, low engagement in pleasant activities, social withdrawal, anxiety, and low social support. Encouraging results have been reported for using Web-based CBT interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 71 publications
(67 reference statements)
0
62
0
Order By: Relevance
“…Bae et al (2009) conducted a need assessment in Korea, where they investigated different types of layout components. Danaher et al (2012) conducted focus group interviews to complement usability testing of a webbased intervention for symptoms of postpartum depression in United States and Australia, and their findings correspond with Tiburcio et al (2016) findings with a preference for images and colours to enhance user experience. Tiburcio et al (2016) conducted usability testing of web-based self-help programmes in Mexico among a sample of people with the comorbid conditions of substance misuse and depression, and discovered that those users preferred additional images and colours as elements to promote usability.…”
Section: Layout (Colours and Images)mentioning
confidence: 71%
See 2 more Smart Citations
“…Bae et al (2009) conducted a need assessment in Korea, where they investigated different types of layout components. Danaher et al (2012) conducted focus group interviews to complement usability testing of a webbased intervention for symptoms of postpartum depression in United States and Australia, and their findings correspond with Tiburcio et al (2016) findings with a preference for images and colours to enhance user experience. Tiburcio et al (2016) conducted usability testing of web-based self-help programmes in Mexico among a sample of people with the comorbid conditions of substance misuse and depression, and discovered that those users preferred additional images and colours as elements to promote usability.…”
Section: Layout (Colours and Images)mentioning
confidence: 71%
“…Among the articles reviewed, seven stated the need for improved instructions to users to enhance usability and promote treatment adherence (Currie et al 2010;Danaher et al 2012;Davidson et al 2014;Ho et al 2016;Kelders et al 2013;Tiburcio et al 2016;Wozney et al 2015). Independently navigating pages, completing online exercises and entering personal information into diary tools are all examples frequently used in e-mental health interventions.…”
Section: Navigation and Instructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies document that people with these mental disorders greatly benefit from Web-based interventions [23,24] and that Web-based interventions represent a low threshold service with a high reach [25]. More recently, two studies found support for the feasibility and usability of Web-based interventions targeting PPD [26,27], but there exist no randomized trials testing the efficacy of PPD interventions. Web-based interventions have been found successful in reaching women of lower socio-economic status, a group typically found to be harder to reach [28].…”
Section: Introductionmentioning
confidence: 99%
“…94,121 Feasibility of web and smartphone based interventions for PPD to address accessibility challenges have been piloted and represent innovative future directions. 122126 Examples of larger selected interventions targeting depression after the first year of life have found that improvement in maternal depression symptoms mediated the effect of family based treatment on toddler externalizing and internalizing symptoms, however this was not specific to PPD. 127 …”
Section: Universal Selected and Indicated Efforts For Maternal Postmentioning
confidence: 99%